To find the equation of the new line after Lucy translates her original line \( y = 3x + 2 \) one unit to the right and two units up, we can follow these steps:
-
Translation to the Right: Translating the line one unit to the right involves replacing \( x \) with \( x - 1 \). Substitute \( x - 1 \) into the original equation: \[ y = 3(x - 1) + 2 = 3x - 3 + 2 = 3x - 1 \]
-
Translation Up: Now, we need to translate the resulting line \( y = 3x - 1 \) two units up. This means we add 2 to the \( y \)-value: \[ y = 3x - 1 + 2 = 3x + 1 \]
So the equation of the new line after the transformations is: \[ y = 3x + 1 \]
Thus, the correct answer is: D. y = 3x + 1.